Hubungan Minat Belajar dengan Hasil Belajar dalam Mata Pelajaran SMAW di SMK Negeri 1 Sumatera Barat - Damrizal Damrizal; Jasman Jasman (Jurnal Pendidikan Teknologi Kejuruan, 2019)
The problem in this study is that students are less interested in learning and seen from the daily results obtained from SMAW subject teachers that the learning outcomes of SMAW subjects in the Welding Engineering department are still low. The purpose of this study is to determine whether there is a relationship between interest in learning and learning outcomes in SMAW subjects. This type of research is descriptive correlational research. The sample stated in this study were all students of class XI of the Welding Engineering Department who participated in the 48 Solid Metal Arc Welding subjects. The results of the study revealed a contribution of a positive relationship between interest in learning with student learning outcomes in the field of study SMAW Class XI Welding Engineering students of SMK Negeri 1 West Sumatra 2018/2019 learning year. This gives the meaning of the higher interest in learning, the higher learning outcomes of SMAW learning outcomes.